Reconstrução mnemônica e diáspora em A Mercy e October de Morrison e Wicomb - Albuquerque, Soraya do Lago (2019)
The objects of study of this paper are the novels A Mercy by Toni Morrison and October by Zoë Wicomb. Both narratives involve traumatic events in the black populations‘ histories, such as the process of enslavement (Morrison) and apartheid (Wicomb). The main goal is to think about the relationship between memory and the feeling of non-belonging caused by the black populations' diaspora, configured, in turn, by forced displacements or not. We intend to show that the two novels in question constitute fictional mnemonic reconstructions that seek to fill the gaps entailed by the diasporic process and its losses. The hypothesis is that the evocation of the diasporic memory gives the characters the possibility of changing their behavior, showing transgressive attitudes which will make them more empowered, through decolonization, in relation to the acquired subordination and passivity of the patriarchal, enslavement and segregationist model. Such transgression indicates the curative potential of those narratives, since there is an overcoming in the moving of the characters‘ performance. We rely on postcolonial and decolonial studies to support our research, since we believe in the possible decoloniality of the stigmata of subalternity instituted for black people.